Seamanship in Barangay Damilisan, Miag-ao, Iloilo, 1970-1999. - Galeos, Jay Neil E.
This is a socio-historical study about the popularity of seamanship profession in Barangay Damilisan Miagao from 1970 to 1999. It aims to: (1) find out why many Damilisanons choose the field of seafaring and work overseas, (2) identify the families in Barangay Damilisan who have seaman member/relative abroad, and (3) find out the contributions of the seamen in the development of Barangay Damilisan or of Miagao as a whole. (p)The study used an interview guide in getting information from the seamen as well as their relatives. For supplementary materials, it also utilized books, newspapers, journals, amgazines, articles, general references, and theses. These materials were visited and consulted in various libraries. Government offices were also consulted for more information. Maritime instructors wer also tapped to explain the importance of their expertise. The data gathered were then organized according to the objectives of the study. (p)There were many reasons why Damilisanons choose the seafaring endeavor. Among these were the good paying nature of the profession, the demand of Filipino seamen abroad, and the influence factor. The influence factor is highly motivated by the economic success of the seamen overseas. Thus, the younger generations followed their fathers' and uncles' profession. (p)The research reveals that the conributions of the seamen in the Barangay ranges from material to immaterial things. These contributions are the great factors on the identity of Barangay Damilisanon as having the most number of seamen in the Municipality of Miagao. (p)The research paper concludes that the continuing number or increase of Damilisanon seamen is highly attributed to the contributionss and socio-economic mobility of the seamen in the area.